Health sciences students' and instructors' perceptions of the emergency switch to virtual internship amid the COVID-19 pandemic: A case from Qatar - Bawadi, Hiba; Abdul Rahim, Hanan; Moawad, Joyce; Shami, Rula; Du, Xiangyun; El-Awaisi, Alla; Al-Moslih, Ayad Moslih Ibrahim; Diab, Mohammad; Al-Jayyousi, Ghadir Fakhri (Frontiers in Medicine, 2022)
In efforts to contain the COVID-19 pandemic, health colleges at Qatar University shifted their clinical training to virtual internships (VI) and project-based learning (PBL). The shift was new to students and faculty alike, and a major change that posed many challenges. This study aimed to explore the experience of changing to VIs during the pandemic from both the clinical instructors’ and health sciences students’ perspectives. A qualitative study was conducted based on the framework of readiness to change. It involved focus group discussions with students from the departments of Public Health and Human Nutrition and in-depth interviews with clinical instructors using appropriate online platforms. A total of 4 focus groups with 20 students and 4 interviews with instructors were conducted. Transcripts were analyzed following the inductive-deductive approach. The major themes that emerged from the analysis described students’ and clinical instructors’ perceptions of the necessity and efficiency of the switch to VI; the design of the VI and the extent of the clinical/field experience and skills that it offered; confidence in the ability to succeed in this type of internship and confidence about reaching expected goals; academic and moral support from clinical faculty and coordinators and the communication process with faculty and preceptors; and finally, the benefits gained and how employers would view this type of internship. Health sciences students’ readiness for VI was generally low. Several student and faculty needs have to be addressed, specifically regarding the design of the program and the level of preceptors’ communication with students. The findings would direct health programs, clinical instructors, and preceptors to better understand students’ needs and efficiently plan for virtual internships during not only emergencies but also whenever there is a need to deliver online experiential learning courses.